Mechanisms of Change in the Relationship between Self‐Compassion, Emotion Regulation, and Mental Health: A Systematic Review. Issue 2 (19th April 2018) - Inwood, Elisa; Ferrari, Madeleine
Abstract : Background: Research suggests that self‐compassion may improve mental health by promoting emotion regulation (Berking & Whitley, 2014 ). This review aimed to identify studies which investigated the relationship between self‐compassion, emotion regulation, and mental health in order to examine the role of emotional regulation as a mechanism of change. Methods: Searches were conducted in PsycINFO, CINAHL, Medline complete, Web of Science and Scopus databases. Inclusion criteria required publications to be: peer reviewed, published in English, contain validated measures of self‐compassion and emotion regulation, and report a direct analysis on the relationship between these constructs. Results: The search yielded five studies which met inclusion criteria. Emotion regulation significantly mediated the relationship between self‐compassion and mental health. This pattern was consistent across community and clinical samples, for a range of mental health symptoms including stress, depression, and post‐traumatic stress disorder. A critical limitation of the review was that all included studies used cross‐sectional data, limiting interpretations regarding causation. Conclusions: Results provide preliminary evidence that emotion regulation may be a mechanism of change in the relationship between self‐compassion and mental health. Self‐compassion may be a pertinent preliminary treatment target for individuals who avoid experiences of emotions.